2020
DOI: 10.1108/ijppm-12-2018-0451
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of capital structure; a sector-level analysis for Indian manufacturing firms

Abstract: PurposeThe purpose of this paper is to empirically analyze the determinants of capital structure and their long-run equilibrium relationships with firm-specific and macroeconomic indicators for Indian manufacturing firms.Design/methodology/approachThe study is conducted using the panel semi-parametric and non-parametric regression models to identify the key determinants of capital structure. Panel cointegration models are also employed for analyzing the long-run equilibrium association of capital structure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
2
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 72 publications
5
32
2
12
Order By: Relevance
“…The positive and insignificant relationship between firm size and capital structure is not in line with the results of the empirical studies of Sofat & Singh (2017) and Panda & Nanda (2020) which state that firm size has a negative relationship to capital structure. The direction of the positive influence between firm size and capital structure is supported by the results of research by Neves et al (2020) and Lemma & Negash (2014) which state that firm size has a positive influence on capital structure.…”
Section: Firm Size and Capital Structurecontrasting
confidence: 73%
See 2 more Smart Citations
“…The positive and insignificant relationship between firm size and capital structure is not in line with the results of the empirical studies of Sofat & Singh (2017) and Panda & Nanda (2020) which state that firm size has a negative relationship to capital structure. The direction of the positive influence between firm size and capital structure is supported by the results of research by Neves et al (2020) and Lemma & Negash (2014) which state that firm size has a positive influence on capital structure.…”
Section: Firm Size and Capital Structurecontrasting
confidence: 73%
“…Based on an empirical study conducted by Sofat & Singh (2017) and Panda & Nanda (2020), firm size has a negative relationship to capital structure. These results are in line with the pecking order theory, which assumes that large companies have the advantage of being able to issue securities rather than using debt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation is found in the research by Fitriyah and Hidayat (2011) who stated that the IOS negatively affects debt policy. Meanwhile, Panda and Nanda (2018) found that the relationship between investment opportunities and debt ratios was negative if using a sample of chemical firms, goods firms, food and agro, textile and transportation companies. In construction, machinery, and metal firm, the relationship between investment opportunities and debt ratio is positive.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kyissima, Xue and Abeid (2019); Tailab (2014); Desmintari and Yetty (2015); Haron (2016); and Vătavu (2015) find that company performance has a negative effect on debt ratio. Meanwhile, Serghiescu and Vaidean (2014); Murtiningtyas (2012); and Panda and Nanda (2018) find that debt ratios have a positive influence on company performance.…”
Section: Introductionmentioning
confidence: 99%